Life's Devices: The Physical World of Animals and Plants - Steven Vogel (University Press, 2000)
Have you ever wondered about the design of plants and animals around us; why a fish swims more rapidly than a duck can paddle, why healthy trees more commonly uproot than break, how a shark manages with such a filmsy skeleton, or how a mouse can easily survive a fall onto any surface from any height. This entertaining and informative book describes how living things bump up against nonbiological reality; it aims to change how you view your immediate surroundings. It will not only fascinate the general reader but will also serve as an introductory survey of biomechanics. Life's Devices includes examples from every major group of animals and plants, with references to recent work, with illustrative problems, and with suggestions of experiments that need only common household materials.